The Canterbury Tales - "Chaucer, Geoffrey" (Longman Group Ltd: Harlow, 1992)
An illustrated retelling of eight of the Canterbury Tales including the "The Nun's Priest's Tale," "The Pardoner's Tale," "The Wife of Bath's Tale," "The Franklin's Tale," "The Knight's Tale," "The Friar's Tale," and "The Clerk's Tale."
Keywords: English language - Readers - For schools